The influence of action video game playing on eye movement behaviour during visual search in abstract, in-game and natural scenes - Azizi, E.; Abel, L. A.; Stainer, M. J, (Attention, Perception, & Psychophysics, 2017)
Action game playing has been associated with several improvements in visual attention tasks. However, it is not clear how such changes might influence the way we overtly select information from our visual world (i.e. eye movements). We examined whether action-video-game training changed eye movement behaviour in a series of visual search tasks including conjunctive search (relatively abstracted from natural behaviour), game-related search, and more naturalistic scene search. Forty nongamers were trained in either an action first-person shooter game or a card game (control) for 10 hours. As a further control, we recorded eye movements of 20 experienced action gamers on the same tasks. The results did not show any change in duration of fixations or saccade amplitude either from before to after the training or between all nongamers (pretraining) and experienced action gamers. However, we observed a change in search strategy, reflected by a reduction in the vertical distribution of fixations for the game-related search task in the action-game-trained group. This might suggest learning the likely distribution of targets. In other words, game training only skilled participants to search game images for targets important to the game, with no indication of transfer to the more natural scene search. Taken together, these results suggest no modification in overt allocation of attention. Either the skills that can be trained with action gaming are not powerful enough to influence information selection through eye movements, or action-game-learned skills are not used when deciding where to move the eyes.